Effects of storage on the oxidative stability of acorn oils extracted from three different Quercus species. (25th July 2020) - Makhlouf, Fatima Z; Squeo, Giacomo; Difonzo, Graziana; Faccia, Michele; Pasqualone, Antonella; Summo, Carmine; Barkat, Malika; Caponio, Francesco
Abstract: BACKGROUND: Acorn fruit and its components and by‐products are receiving renewed interest due to their nutritional and phytochemical features. In particular, the oil extracted from acorns is recognized for having high nutritional quality and for being rich in bioactive compounds. Despite the growing interest, few papers are available that consider the evolution of acorn‐oil characteristics during storage. Our aim was to investigate the storage‐related changes in acorn oils extracted from three Quercus species grown in Algeria ( Q. ilex, Q. suber, and Q. coccifera ) 180 days after production, with a focus on polar and volatile compounds, not yet investigated. Basic quality parameters, phenolic content, antioxidant activity and induction time were also monitored. RESULTS: The oxidation markers (peroxide value and UV absorptions) increased during storage, whereas antioxidants decreased. A distinctive volatile profile was observed at the time of production, which underwent changes during storage. Polar compounds increased, whereas induction time decreased. The oil extracted from Quercus suber L. was the most affected by storage time. CONCLUSION: Floral and fruity volatile compounds detected in the oils' headspace could explain the pleasant flavor of acorn oils reported by other authors. As with other vegetable oils, storage depletes both volatiles and antioxidants and produces oxidation compounds, such as oxidized triacylglycerols. However, the acorn oils that were studied were quite stable under storage in the dark at room temperature for 6 months. © 2020 Society of Chemical Industry